2015
DOI: 10.1111/dpr.12121
|View full text |Cite
|
Sign up to set email alerts
|

A Less Gendered Access to Land? The Impact of Tanzania's New Wave of Land Reform

Abstract: Contemporary land reforms in sub-Saharan Africa tend to be evaluated based on the state-centric reforms of the past, which disadvantaged women. However, this article argues that the new-wave of land reforms and their decentralised administration institutions and anti-discriminatory legal frameworks may be different. Based on field research on the implementation of Tanzania's 1999 Land Acts, it identifies an institutional reconfiguration in which the formal institutions are gradually strengthened and the custom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…This implies that farmer entrepreneurship is a male-dominated sector, although women are often observed to be more involved in downstream agricultural activities in developing countries. This finding is in line with earlier research which found that women are usually disadvantaged in agriculture due to uneven access to land, especially in Asian countries [ 86 , 87 ].…”
Section: Resultssupporting
confidence: 92%
“…This implies that farmer entrepreneurship is a male-dominated sector, although women are often observed to be more involved in downstream agricultural activities in developing countries. This finding is in line with earlier research which found that women are usually disadvantaged in agriculture due to uneven access to land, especially in Asian countries [ 86 , 87 ].…”
Section: Resultssupporting
confidence: 92%
“…In the past, resettlement programs, redistributive land reforms, and land titling projects have generally assigned the majority of farmland to men as household heads, thereby further deteriorating women's rights to land (Lastarria-Cornhiel et al 2014;Meinzen-Dick and Mwangi 2008;Quisumbing et al 2001). More recently, policy makers have intentionally designed land reforms to improve gender equality-for example, by automatic or compulsory joint titling of land by spouses (see, for example, Ali, Deininger, and Goldstein 2014;Lastarria-Cornhiel et al 2014;Pedersen 2015;Wiig 2013).…”
Section: Gender and The Role Of The Statementioning
confidence: 99%
“…For example, in many least developed countries such as Tanzania, this primary focus on rights-based access is understandable given longstanding gender inequality in land rights and security of tenure that may constrict livelihood diversification and thereby limit adaptation options (Mbilinyi 2003; Ikdahl 2008; Peterman 2011). Although Tanzania’s new land laws in 1999 sought to explicitly increase women’s land access and security of tenure, women of lower social standing continue to face considerable obstacles in pursuing and maintaining land claims through village councils (Pedersen 2015). In light of this, we argue for a focus on unequal access that encompasses the “wider range of social relationships that constrain or enable people to benefit from resources without focusing on property relations alone,” including structural determinants of access such as knowledge, technologies, and authority (Ribot and Peluso 2003, p. 154).…”
Section: Introductionmentioning
confidence: 99%